A case of minimal change disease during pregnancy – benefits of early diagnosis and use of corticosteroids. (September 2022) - Sagar, Priyanka S; Fischer, Eddy; Gangadharan Komala, Muralikrishna; Bose, Bhadran
Nephrotic syndrome presenting in pregnancy is rare and poses a diagnostic and therapeutic challenge. Timing of renal biopsy is important given the increased risk of bleeding and miscarriage, and the choice of immunosuppression is limited due to the teratogenicity profiles of standard drugs. We report and discuss a case of minimal change disease diagnosed by renal biopsy during early pregnancy and treated with corticosteroids throughout the pregnancy. Prompt diagnosis and treatment of glomerular disease in pregnancy are vital to prevent poor maternal and fetal outcomes.